NBS1 facilitates preribosomal RNA biogenesis - Man Luo; Xiaochun Yu (Proceedings of the National Academy of Sciences, 2025)
Mutations in the NBS1 gene result in Nijmegen breakage syndrome (NBS), and the gene encodes NBS1 that forms a complex with MRE11 and RAD50 and participates in DNA damage repair. However, the molecular mechanism by which NBS1 mutations cause clinical phenotypes of NBS, such as craniofacial dysmorphism, is still unclear. Here, we show that NBS1 localizes at the ribosomal DNA (rDNA) loci in nucleoli and interacts with ribosomal RNA (rRNA) transcription machinery including RNA polymerase I (Pol I) and TCOF1. Loss of NBS1 impairs Pol I-dependent transcription of pre-rRNA and induces nucleolar stress. In particular, lacking Nbs1 in mouse neural crest cells not only leads to the reduction of ribosome biogenesis but also craniofacial abnormalities during prenatal development. Moreover, the C-terminus of NBS1 is associated with pre-rRNA and a number of pre-rRNA processing factors, which may also facilitate pre-rRNA maturation. Taken together, our study reveals the functions of NBS1 in rRNA biogenesis.